Development of system-type-centric paradigm of computer-software systems architectural design for automation systems - Polataiko, Ihor; Zamikhovskyі Leonid (Technology audit and production reserves, 2026)
The object of research is the design processes of computer-software systems in the automation domain. Computer-software systems are considered as a combination of software and hardware. This research focuses on addressing the lack of a formal methodology that differentiates the architectural design of computer-software systems for automation systems, including in hybrid Information Technology/Operational Technology environments. Existing approaches, methods, and models for designing the architecture of computer-software systems do not account for the differentiation of approaches based on the fundamental differences in the nature of various system types used in the automation domain. This precludes the establishment of standardized and differentiated processes and methods for designing the architecture of such systems. The main result is a new type-centric paradigm of architectural design, based on a taxonomy that classifies computer-software systems into fundamental types by their architectural nature. Furthermore, within the scope of the research, the levels and elements of computer-software systems are defined, which forms a standardized vision of the systems’ constituent parts. In contrast to existing models, approaches, and methodologies, the proposed type-centric paradigm for the architectural design of computer-software systems incorporates the fundamental aspects of the systems’ nature that are important for architectural design, classifying systems based on this factor. The proposed paradigm provides a foundation for systematized, specialized, and differentiated architectural design processes adapted to the specifics of the systems’ nature. This ensures standardization, interoperability, and systematicity in the design of computer-software systems for automation systems, potentially forming a basis for automated architectural design systems.